Anchoring effect of hyperbranched carborane in highly cross-linked cyclosiloxane networks toward high-performance polymers - Yu, Chongwen (2023)
High-performance polymers (HPPs) have good thermal and mechanical properties even under harsh environments and are widely used in aerospace, microelectronics, automobile, and other fields. Traditional employed highly cross-linked HPPs tend to fail in their performance at high temperatures due to the structural defects, which remains a challenge in both scientific investigation and engineering applications for decades. Herein, we employed a cyclosiloxane hybrid polymer (CHP) to investigate a new design strategy to compensate for the structural defects in the highly cross-linked network, which avoids catastrophic failure at high temperatures. Hyperbranched o-carborane was synthesized and used to compensate for structural defects of CHP. The antioxidant ability and toughness of CHP were improved, and it had better mechanical properties over a wide temperature range. Moreover, the anchoring effect of hyperbranched o-carborane in the cyclosiloxane network was systematically investigated. The hyperbranched o-carborane cage could stabilize the CHP network under dynamic thermal stress through anchoring the dangling bonds, and the highly cross-linked network suppressed the disintegration of the o-carborane cage by anchoring boron atoms of the o-carborane cage. Furthermore, the structural evolution mechanism of the o-carborane cage with increasing temperature was proposed. This fundamental research provided new insights into the design of HPPs for harsh environments.